Felipe Herrera: Notes for the History of His Economic Thought, 1945-1960 [Felipe Herrera: Notas Para la Historia de Su Pensamiento Económico, 1945-1960] - Ross-Orellana, C (Universidad de Talca, 2013)
This paper studies the economic thought of Felipe Herrera Lane, from the perspective of political economy and by crossing three dimensions: His intellectual biography, its international role and his intellectual work. The latter is the basis for a research like this, but nourishes and complements the previous two.